Visual three-dimensional spatial distribution of motor neurons innervating superficial limb muscles in mice - Qi, Zhidan; Han, Shuai; Wang, Shen; Gu, Xinyi; Deng, Jin; Huang, Chen; Yin, Xiaofeng (Frontiers in Cellular Neuroscience, 2022)
The coordination of motor function in the spinal cord depends on selective connections between distinct classes of motor neurons and their target muscles.However, knowledge regarding the anatomical connections between the superficial limb skeletal muscles and the motor neurons that innervate them is limited.In this study, with combination of the multiple retrograde tracing method compatible with 3 DISCO clearing, we explored the spatial distribution of different motor neuron pools targeting specific superficial muscles of four limbs in mouse spinal cords, which was dominated by the radial, median, ulnar or sciatic nerve. This work reveal the precise interrelationship among different motor neuron pools innervating limb function under the same space and time. The data will help to further understand the neural loop and muscular motor coordination.